Analisis Pengelolaan Limbah Medis Padat di Puskesmas Kasimbar Kecamatan Kasimbar Kabupaten Parigi Moutong, Sulawesi Tengah - Kantohe, Imelda; Restawan, I Gede; Madude, Meilin Anggreyni (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
Based on initial data collection at the Kasimbar Health Center, Kasimbar District, Parigi Moutong Regency, it was obtained that the Health Center had managed solid medical waste, officers admitted that they still used mercury sphygmomanometers provided by the Health Center. The purpose of this study was to determine the management of solid medical waste at the Kasimbar Health Center, Kasimbar District, Parigi Moutong Regency. This type of research is a qualitative descriptive study with variables of solid medical waste containers, solid medical waste collection, solid medical waste transportation and temporary shelters. The types of data obtained are primary data and secondary data. Data analysis using data reduction, data presentation and drawing conclusions. The population in this study were all solid medical waste management officers at the Kasimbar Health Center, totaling 2 sanitarian officers. The sample used in this study was a saturated sample of medical waste management officers. In this study, the sample used was 2 respondents from the Kasimbar Health Center sanitarian officers. The results of the study indicate that the process of managing solid medical waste at the Kasimbar Health Center is in accordance with the applicable provisions of the Regulation of the Minister of Health of the Republic of Indonesia Number 18 of 2020 concerning the Management of Medical Waste at Regional-Based Health Service Facilities. The conclusion in this study is that the process of managing solid medical waste at the Kasimbar Health Center is in accordance with the provisions, namely starting from storage, collection, transportation and temporary storage, all of which are processed quite well, only in the transportation process the cleaning service does not use a trolley as a means of transportation.